Developing consensus for culturally informed forensic mental health assessment: Experts' opinions on best practices - Fanniff, Amanda M; York, Taylor; Gutierrez, Renee (Law and human behavior, 2023)
Individuals with minoritized identities are overrepresented in legal system contexts; thus, forensic mental health professionals conduct evaluations of examinees with a diversity of identities. Professional and ethical guidelines direct that these evaluations be completed in a culturally informed manner, yet many professionals still identify a need for specific guidance on how to do so. In the present study, we sought to establish consensus regarding best practices in incorporating culture into forensic mental health evaluations. Given the exploratory nature of this research, no formal hypotheses were tested. We expected that participants would concur that some practices are important to completing culturally informed forensic evaluations. We recruited two samples. Nine people with joint expertise in cultural considerations and forensic evaluations participated in a Delphi-type poll. More than half reported a minoritized racial/ethnic identity, and all identified as a man (56%) or woman (44%). Experts were surveyed regarding importance (two rounds) and relevance (one round) of recommended practices. They contributed seven additional relevant practices. Twenty-one board-certified forensic psychologists completed a one-time survey of their perceptions of best practices. These psychologists primarily identified as White (90%), and most did not identify as Hispanic or Latine (80%). They all identified as men (45%) or women (55%). This sample was asked to rate the importance of a list of practices refined during the Delphi-type poll. The majority of practices were considered important or very important by experts and board-certified psychologists. Consensus is most clear for 28 practices with means, medians, and modes all in the "important" to "very important" range at all time points. There is wide agreement on the importance of particular methods for incorporating cultural considerations in each phase of the forensic evaluation process. Forensic psychologists can use this information to self-evaluate and improve their practice and to inform training. (PsycInfo Database Record (c) 2023 APA, all rights reserved).